Intelligent image analysis for plant phenotyping - Samal, Ashok; Choudhury, Sruti Das (Boca Raton, FL : CRC Press, 2021)
"Domesticated crops are the result of artificial selection for particular phenotypes and, in some case, natural selection for an adaptive trait. Intelligent Image Analysis for Plant Phenotyping reviews information on time-saving techniques using computer vision and imaging technologies. These methodologies provide an automated, non-invasive and scalable mechanism to define and collect plant phenotypes. Beautifully illustrated with numerous color images, this book is invaluable for those working in the emerging fields at the intersection of computer vision and plant sciences"--
3.6.5 Image Transformations -- 3.6.6 Segmentation -- 3.6.6.1 Frame Difference Segmentation -- 3.6.6.2 Color-Based Segmentation -- 3.6.7 Morphological Operations -- 3.6.7.1 Dilation and Erosion -- 3.6.7.2 Opening and Closing -- 3.6.8 Thinning -- 3.6.9 Connected Component Analysis -- 3.6.10 Skeletonization -- 3.6.10.1 Graphical Representation -- 3.7 Feature Computation -- 3.7.1 Basic Shape Properties -- 3.7.1.1 Length -- 3.7.1.2 Area -- 3.7.1.3 Bounding Box -- 3.7.1.4 Aspect Ratio -- 3.7.1.5 Convex Hull -- 3.7.1.6 Circularity -- 3.7.1.7 Straightness -- 3.7.2 Color Properties
OCLC-licensed vendor bibliographic record.
Keywords: Image processing -- Digital techniques; Computer vision; Phenotype; COMPUTERS / Computer Graphics / General; SCIENCE / Life Sciences / Botany; SCIENCE / Life Sciences / General